Developing an Android-Based E-Module Integrating Banten Local Wisdom to Enhance Sixth-Grade Students’ Conceptual Understanding - Ayu Uswah Munjiah; Yus Rama Denny; Lusiani Dewi Assaat; Mardyanto Barumbun (Universitas Syiah Kuala, 2026)
Elementary school students’ conceptual understanding in natural and social sciences learning, particularly on the topic of Indonesian cultural heritage, remains relatively low. This condition is influenced by the abstract nature of the material, while classroom instruction is still largely dominated by teacher-centered lecture methods. As a result, students are less actively engaged and experience difficulties in understanding the material in depth. In addition, the use of digital-based learning media is still limited and has not sufficiently connected the material to real-life contexts and local wisdom. Consequently, learning becomes less engaging and less meaningful for students. This study aims to develop an Android-based e-module that integrates Baduy local wisdom with the problem-Based learning (PBL) model, as well as to examine its feasibility, practicality, and effectiveness in improving students’ conceptual understanding. This research employs a research and development method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were 20 sixth-grade students. Data were collected through observation, interviews, questionnaires, and pretest–posttest assessments, and then analyzed using Aiken’s V coefficient and the N-gain test.The results indicate that the developed e-module has a feasibility level of 0.73, is considered practical by both teachers and students, and is effective in improving conceptual understanding, as shown by an N-gain score of 0.76 in the high category. Therefore, this e-module can serve as a more contextual, interactive, and meaningful learning solution